Assessment of the Phytotoxicity and Antifeedant Properties of Aristolochia bracteolata Lamk. Leaf Extracts and their Derivatives against the Spotted Bollworm, [Eariasvittella (Fab.)], (Lepidoptera: Noctuidae) - Pavunraj, M.; Ramasubbu, G.; Ezhumalai, P.; Nagarajan, K.; Rajeshkumar, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The phytopesticidal effects of various solvent crude extracts and isolated fractions from the leaves of Aristolochia bracteolata, which were tested for their antifeedant and larvicidal activities on the fourth instar larvae of the shoot and fruit of Earias vittella.The antifeedant and larvicidal activities were performed by fruit disc no-choice methods at 0.625, 1.25, 2.5, and 5% and 125, 250, 500, and 1,000 ppm concentrations for crude and fractions, respectively. The dichloromethane (DCM) extract of A. bracteolata exhibited the maximum antifeedant (61.10%) and larvicidal (65.33%) activities at 5% concentration against E. vittella, followed by hexane (44.93%), acetone (40.40%) and aqueous (22.25%) extracts. It was subjected to fractionation using silica gel column chromatography with different combinations of hexane and ethyl acetate used as the mobile phase. Among the six fractions obtained, fraction 6 showed the maximum antifeedant (78.32%) and larvicidal (81.77%) activities against E. vittella at a 1000 ppm concentration. The preliminary phytochemical analysis of the plant also showed alkaloids, anthroquinones, diterpenoids, flavonoids, glycosides, polyphenols, saponins, steroids, and tannins in the extract. A. bracteolata leaves could be complemented with an eco-friendly pesticide/insecticide for an integrated pest management strategy.